2015
DOI: 10.1111/1467-8551.12106
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of a Stigmatized Practice: A Study of Competitive Intelligence

Abstract: Studies on the diffusion of practices provide valuable insights into how organizations adopt, adapt, sustain and abandon practices over time. However, few studies focus on how stigmatized practices diffuse and persist, even when they risk tainting the adopters. To address this issue and understand how firms manage stigmatized practices, we study US organizations associated with the practice of competitive intelligence (CI) between 1985 and 2012. CI includes legitimate information gathering practices that are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 99 publications
1
32
0
Order By: Relevance
“…Legacy systems impede the implementation of BA. Our study has supported the findings of Reinmoeller and Ansari (2015) in that the role of stigmatised practices and legacy systems have reduced the benefits that could have been derived with business analytics otherwise.…”
Section: Managerial Implicationssupporting
confidence: 84%
See 2 more Smart Citations
“…Legacy systems impede the implementation of BA. Our study has supported the findings of Reinmoeller and Ansari (2015) in that the role of stigmatised practices and legacy systems have reduced the benefits that could have been derived with business analytics otherwise.…”
Section: Managerial Implicationssupporting
confidence: 84%
“…Many characteristics of a technology can influence its adoption (Reinmoeller and Ansari, 2015;Rogers 1995;Li 2008;Thong 1999;Tornatzky and Fleischer, 1990;Wang et al 2010;Zhu et al 2006). These include complexity of technologies, compatibility with practices already existing in a firm, perceived benefits, emergence of big-data computing platforms, and technologies that help increase the security of big-data.…”
Section: Technological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is a lot of potential impact for predictive analytics and data-driven strategies in these settings (cf. Reinmoeller and Ansari, 2016;Sheng, Amankwah-Amoah and Wang, 2017). For example, Sheng, Amankwah-Amoah and Wang (2017), in their review study, have found that public services and administration can benefit from big data for e-voting and e-government (e.g.…”
Section: Differing Levels Of Maturitymentioning
confidence: 99%
“…Both before and after official recognition, organizations might draw upon a repertoire of strategies to deflect organizational stigma (Durand & Vergne, 2015;Reinmoeller & Ansari, 2016). Organizations confronting stigmatization often discursively reframe practices to deflect stigma (e.g.…”
Section: Introductionmentioning
confidence: 99%